2014
DOI: 10.1039/c4ra05124f
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and optical properties of chair-like and boat-like graphane

Abstract: We have studied two favorable conformations of graphane, the chair-like graphane and boat-like graphane. In the chair-like, the H atoms attached to the C atoms alternate on both sides of the sheet while in the boatlike, the C bonded H atoms alternate in pair. Both conformations of graphane have a 2D puckered honeycomb like structure with one hydrogen atom bonded covalently (sp 3 ) to each carbon atom. The chair-like belongs to the P 3m1 (164)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…As a consequence, there are bound exciton states considerably below the conduction band minimum. For graphane the exciton binding energy has been calculated to be 1.6 eV which produces an optical gap of about 3.8 eV . A more complete exciton spectrum is shown in Figure (a).…”
Section: Properties Of Graphanementioning
confidence: 99%
“…As a consequence, there are bound exciton states considerably below the conduction band minimum. For graphane the exciton binding energy has been calculated to be 1.6 eV which produces an optical gap of about 3.8 eV . A more complete exciton spectrum is shown in Figure (a).…”
Section: Properties Of Graphanementioning
confidence: 99%
“…we have addressed ourselves for comprehensive theoretical calculations based on the density functional theory ( DFT ) within all-electron full potential method and the semiclassical Boltzmann theory as incorporated in BoltzTraP code[30] phases. First-principles calculation is one strong and useful tool to predict the crystal structure and its properties related to the electron configuration of a material before its synthesis[31][32][33][34]. First-principles calculation is one strong and useful tool to predict the crystal structure and its properties related to the electron configuration of a material before its synthesis[31][32][33][34].…”
mentioning
confidence: 99%
“…It was found that the increased surface area and the highly conductive surface of graphene could accelerate the generation of hydrogen [39], since the excited electron transfer and separation are limiting factors in the photocatalytic conversion process. Reshak et al studied the different conformations of graphene and calculated the values of energy gap and the bond lengths [40,41].…”
Section: Introductionmentioning
confidence: 99%